PELAKSANAAN FUNGSI PENGAWASAN OMBUDSMAN RI PERWAKILAN SUMATERA BARAT TERHADAP PELAYANAN PUBLIK - M Rafi Ariansyah; Rahmadani Yusran (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study aims to determine the implementation of the oversight function of the Ombudsman RI Representatives of West Sumatra on public services and also to determine the inhibiting factors for the implementation of the supervision of the Ombudsman RI Representatives of West Sumatra to public services in West Sumatra Province. This research uses a qualitative approach with descriptive methods. The results of this study are: 1. Implementation of the oversight function of the Indonesian Ombudsman Representative of West Sumatra on public services in West Sumatra Province which is carried out in 2 (two) fields, namely the field of report inspection and the field of prevention. In the field of report examination, the Indonesian Ombudsman Representative of West Sumatra receives reports, checks reports, follows up reports, carries out investigations, provides recommendations, and conducts monitoring. Meanwhile, in the field of prevention, the Indonesian Ombudsman, the West Sumatra Representative, has made efforts to prevent maladministration by empowering the community which aims to increase public awareness so that they can work together with the Indonesian Ombudsman Representative of West Sumatra in overseeing the implementation of public services in West Sumatra Province. 2. Inhibiting factors in the implementation of the supervision of the Indonesian Ombudsman Representative of West Sumatra on public services in West Sumatra Province is that the Ombudsman finds obstacles and obstacles in the form of a lack of human resources, the absence of a representative Ombudsman in the Regency / City, and a lack of budget